2021
DOI: 10.3390/coatings11050558
|View full text |Cite
|
Sign up to set email alerts
|

Glossiness Evaluation of Coated Wood Surfaces as Function of Varnish Type and Exposure to Different Conditions

Abstract: The objective of this study was to evaluate the glossiness of black alder wood (Alnus glutinosa L.) samples coated with two varnish types as a function of exposure to dry heat and artificial aging. The chemical resistance of the coated samples to cold liquids was also evaluated. Based on the findings in this work, it appears that the varnish types and their structural differences influenced the overall glossiness of the coated samples. The UV varnish exhibited higher gloss values than those coated with the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…In a recent study conducted by Salca et al, alternative ecological products, including water based and UV varnishes, that are widely used due to their low emissions, rapid application, and good gloss retention were investigated, and it was concluded that the UV varnish coated samples exhibited higher gloss values than the water-borne products. [87].…”
Section: Voc Emission Reduction and Suggestionsmentioning
confidence: 99%
“…In a recent study conducted by Salca et al, alternative ecological products, including water based and UV varnishes, that are widely used due to their low emissions, rapid application, and good gloss retention were investigated, and it was concluded that the UV varnish coated samples exhibited higher gloss values than the water-borne products. [87].…”
Section: Voc Emission Reduction and Suggestionsmentioning
confidence: 99%
“…Spectroscopic techniques such as Fourier Transform Infrared Spectroscopy (FTIR) [15,16], Fourier Transform Infrared Spectroscopy-Attenuated Total Reflectance (FTIR-ATR) [17], and/or Fourier Transform Near Infrared Spectroscopy (FT-NIR) [18][19][20] are often used to investigate changes in functional groups of wood chemical components. Other aspects frequently assessed while evaluating the weathering process of materials include the determination of the surface roughness [21,22], wettability [23,24], or glossiness [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of covered modification processes and the scope of applications proved that wood modification is not only the sole concern of a few wood scientists but it became a truly inter-disciplinary research area. Novel formulations, characterization methods, and serviceability are presented and deeply discussed in several publications contributing to the Special Issue [2][3][4][5][6][7]. A broad portfolio of characterization methods can be successfully implemented for the evaluation of complex mechanisms of deterioration process occurring during service life.…”
mentioning
confidence: 99%
“…A broad portfolio of characterization methods can be successfully implemented for the evaluation of complex mechanisms of deterioration process occurring during service life. Artificial [2,3], natural [4,5], and combined [6] weathering methods are used for the assessment of the performance of different substrates and coatings. The performance of wood finished with a broad range of coatings systems is highly improved when compared to that of unmodified wood.…”
mentioning
confidence: 99%
See 1 more Smart Citation